Integrating the “Curriculum of Love” into English Language Education - Kuswanto, Welly (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The integration of character education into language teaching has become a major concern in Islamic education discourse in Indonesia, particularly in response to social polarization, moral erosion, and religious intolerance. The Ministry of Religious Affairs has introduced the Curriculum of Love to instill values of love for God, humanity, nature, and the nation in all subjects, including English language education. This study aims to investigate how the Curriculum of Love is internalized through English language teaching and what pedagogical strategies and materials are used to support this integration at Pondok Pesantren Dalwa, East Java. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis. The results of the study indicate that teachers at Pondok Pesantren Dalwa successfully integrated the values of the Love Curriculum into English language instruction through contextualization of materials, reflective dialogue, journal writing, and ethical discussions. This strategy not only increases student engagement but also encourages deeper moral reflection, transforming English language learning into a holistic educational tool. However, challenges such as a lack of teacher training and relevant materials still exist. This study contributes to the field of spirituality-based English language teaching, reinforcing the potential of English language education as a means of fostering communicative competence as well as ethical and national awareness.